A priori checking of the light‐response and data quality before extended data collection in pump–probe photocrystallography experiments. Issue 1 (23rd January 2017) - Coppens, Philip; Makal, Anna; Fournier, Bertrand; Jarzembska, Katarzyna N.; Kamiński, Radosław; Basuroy, Krishnayan; Trzop, Elzbieta
Abstract : In picosecond and slower pump–probe diffraction experiments the collection of response–ratio correlation sets prior to full data collection provides an invaluable confirmation of the existence of a light‐induced signal prior to full data collection. If a response to light exposure is observed, the quality of the data being collected can be assessed. Abstract : In picosecond and slower pump–probe diffraction experiments, collection of response–ratio correlation sets prior to full data collection provides an invaluable confirmation of the existence of a light‐induced signal prior to full data collection. If a response to light exposure is observed, the quality of the data being collected can be assessed. A number of such correlation plots both for synchrotron and in‐house pump–probe data collection are presented.